PENERAPAN MODEL PEMBELAJARAN MEMORI UNTUK MENINGKATKAN DAYA INGAT PESERTA DIDIK - Andi Jusriana (Faculty of Tarbiyah and Teacher Training, 2022)
This study aims to describe whether there are differences in the memory abilities of students who are taught and not taught using the memory learning model in class X MIA SMAN 2 Sinjai. The research design used was the matching only posttest only control group design with two classes, one experimental class and one comparison class. The students' recall ability was measured using a recall ability test which was validated by two validators after the application of each model. The results of the descriptive study showed that the average value of the memory ability of students who were taught using the memory learning model was 78.4 in the high category with a percentage of 54.5%. In the comparison class, the average value of 70.2 was obtained in the medium category with a percentage of 40.9%. Furthermore, based on the results of statistical analysis for the ability to remember students, it shows that the memory learning model can improve the memory skills of students in class X MIA SMA Negeri 2 Sinjai. The implication of this study is that the results of this study indicate that the application of the memory learning model can improve students' memory skills and for further researchers, the results of this study can be used as comparison and reference material to find other learning models that can improve students' memory skills.